Internal structure and origin of modern salt crust of Salar de Uyuni (Bolivia) salt pan based on tomographic research - BURLIGA, Stanisław; DOHNALIK, Marek (Geology, Geophysics and Environment, 2011)
This paper presents the results of a study on the internal structure of modern salt crust of Salar de Uyuni in SW Bolivia. Additionally, the structure of desiccation fissure infill was investigated. X-ray microtomography was used as the main analytical method because it enabled the complete structure of the sample’s interior to be imaged without its destruction. Based on microtomographic images three layers were distinguished in the crust between the surface and its base: a halite shell at the top, a cellular halite layer in the middle and a large-pore halite layer at the base. Results revealed that the desiccation fissures are filled with extremely porous bubble-halite. Distribution of mud in the sample as well as wash-out of the surfical halite crystals indicate the cyclicity of halite dissolution, its crystallisation and mud accumulation. These observations provide an explanation for low rate salt accumulation in the salt pan. This leads to the conclusion that the observed layering in the rocks does not reflect annual sedimentation-evaporation cycles but rather long-term cycles.